Waterlicht & Dune - Roosegaarde, Daan 1979- (urbanNext, 2017)
Waterlicht is the dream landscape about the power and poetry of water. As a virtual flood, it shows how high the water could reach without human intervention. Waterlicht, also known as (3z(Bthe Northern Light of the Netherlands(3y (Bexperiences the flood channel of the river IJssel near Westervoort. Waterlight reveals the invisible artworks of the Netherlands, and will appear throughout the Netherlands in the coming years.s
Daan Roosegaarde, Kerb23, Middle Density, Project, Senseable Technologies, Technology and fabrication
Active Public Spaces, Agency of Urban Organization, Art&technology, Artificial nature, Built environment, Citizen interaction, Illusion, Installation, LED, Lighting design, Multidisciplinary, Nature, Paris, Project, Public space role, Technological Approach, Technopoetry, The Netherlands
Excerpt from Kerb23 produced by the RMIT University School of Architecture and Design.
Keywords: Architecture; Exhibition; Installation; Water; the Netherlands